A robust adaptive control system for high performance aircraft / Tiauw Hiong Go (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2009)
The design of a longitudinal controller to enhance the maneuverability of a high performance aircraft is described. Since such aircraft is often required to fly outside the linear aerodynamic regimes, the design is based on the nonlinear equations of motion. The controller is of adaptive type and it is robust with respect to unknown, but bounded uncertainties. The performance of the resulting controller is evaluated through simulations using hypothetical fighter aircraft parameters. The controller is demonstrated to be able to obtain good and consistent performances over a wide range of flight conditions.